The coffee material culture (2020)
It aims to identify the objects that are part of the material culture coffee to give them more value and recognition, based on theoretical analysis of issues have been addressed the issue, as well as field research where they have personally taken testimony and photographs material that was later used as analysis to synthesize the information contained in maps and diagrams to identify the elements and rituals that are part of domestic and from practices work activity that takes place in the context of coffee production .Among the conclusions is stated the classification of objects into new categories such as those developed and reused, there was a significant experience of religiosity and the recognition of the significance of objects from the traditions founded.